"Something's Afoot" Post-Show at Mercedes Edwards Theater at Clark Intermediate School - Watkins, Howard::::::::: (1987)
Katie Rea receiving bouquet of flowers from Robin Watkins Leslie Prusia, Christine Watkins, Adam Watkins and Frances Kamp in background